Plasmid content of carbapenem resistant Acinetobacter baumannii isolates belonging to five International Clones collected from hospitals of Alexandria, Egypt - Sánchez-Urtaza, Sandra; Ocampo-Sosa, Alain; Rodríguez-Grande, Jorge; El-Kholy, Mohammed A.; Shawky, Sherine M.; Alkorta, Itziar; Gallego, Lucia (Frontiers in Cellular and Infection Microbiology, 2024)
Multidrug resistant Acinetobacter baumannii is one of the most important nosocomial pathogens worldwide. During the last decades it has become a major threat for healthcare settings due to the high antibiotic resistance rates among these isolates. Many resistance determinants are coded by conjugative or mobilizable plasmids, facilitating their dissemination. The majority of plasmids harbored by Acinetobacter species are less than 20 Kb, however, high molecular weight elements are the most clinically relevant since they usually contain antibiotic resistance genes. The aim of this work was to describe, classify and determine the genetic content of plasmids harbored by carbapem resistant A. baumannii isolates belonging to predominant clonal lineages circulating in hospitals from Alexandria, Egypt. The isolates were subjected to S1-Pulsed Field Gel Electrophoresis experiments to identify high molecular weight plasmids. To further analyze the plasmid content and the genetic localization of the antibiotic resistance genes, isolates were sequenced by Illumina Miseq and MinION Mk1C and a hybrid assembly was performed using Unicycler v0.5.0. Plasmids were detected with MOBsuite 3.0.3 and Copla.py v.1.0 and mapped using the online software Proksee.ca. Replicase genes were further analyzed through a BLAST against the Acinetobacter Plasmid Typing database. Eleven plasmids ranging in size from 4.9 to 205.6 Kb were characterized and mapped. All isolates contained plasmids, and, in many cases, more than two elements were identified. Antimicrobial resistance genes such as blaOXA-23, blaGES-like, aph(3’)-VI and qacEΔ1 were found in likely conjugative large plasmids; while virulence determinants such as septicolysin or TonB-dependent receptors were identified in plasmids of small size. Some of these resistance determinants were, in turn, located within transposons and class 1 integrons. Among the identified plasmids, the majority encoded proteins belonging to the Rep_3 family, but replicases of the RepPriCT_1 (Aci6) family were also identified. Plasmids are of high interest as antibiotic resistance control tools, since they may be used as genetic markers for antibiotic resistance and virulence, and also as targets for the development of compounds that can inhibit transfer processes.